45 Long-term Treatment with Deutetrabenazine Is Associated with Continued Improvement in Tardive Dyskinesia: Results from an Open-label Extension Study. (12th March 2019) - Hauser, Robert A.; Fernandez, Hubert H.; Stamler, David; Davis, Mat D.; Factor, Stewart A.; Jimenez-Shahed, Joohi; Ondo, William G.; Jarskog, L. Fredrik; Woods, Scott W.; LeDoux, Mark S.; Shprecher, David R.; Anderson, Karen E.
Abstract: Study Objective: To evaluate long-term efficacy of deutetrabenazine in patients with tardive dyskinesia (TD) by examining response rates from baseline in Abnormal Involuntary Movement Scale (AIMS) scores. Preliminary results of the responder analysis are reported in this analysis. Background: In the 12-week ARM-TD and AIM-TD studies, the odds of response to deutetrabenazine treatment were higher than the odds of response to placebo at all response levels, and there were low rates of overall adverse events and discontinuations associated with deutetrabenazine. Method: Patients with TD who completed ARM-TD or AIM-TD were included in this open-label, single-arm extension study, in which all patients restarted/started deutetrabenazine 12mg/day, titrating up to a maximum total daily dose of 48mg/day based on dyskinesia control and tolerability. The study comprised a 6-week titration and a long-term maintenance phase. The cumulative proportion of AIMS responders from baseline was assessed. Response was defined as a percent improvement from baseline for each patient from 10% to 90% in 10% increments. AlMS score was assessed by local site ratings for this analysis. Results: 343 patients enrolled in the extension study (111 patients received placebo in the parent study and 232 patients received deutetrabenazine). At Week 54 (n=145; total daily dose [mean±standard error]: 38.1±0.9mg), 63% of patients receiving deutetrabenazine achieved ≥30% response, 48% of patients achieved ≥50% response, and 26% achieved ≥70% response. At Week 80 (n=66; total daily dose: 38.6±1.1mg), 76% of patients achieved ≥30% response, 59% of patients achieved ≥50% response, and 36% achieved ≥70% response. Treatment was generally well tolerated. Conclusions: Patients who received long-term treatment with deutetrabenazine achieved response rates higher than those observed in positive short-term studies, indicating clinically meaningful long-term treatment benefit. Presented at: American Academy of Neurology Annual Meeting; April 21–27, 2018, Los Angeles, California, USA. Funding Acknowledgements: This study was supported by Teva Pharmaceuticals, Petach Tikva, Israel.